The Influence of Perceived Ease of Use, Perceived Security, Perceived Behavioral Control, and Behavioral Nudges on Digital Payment Adoption in Jakarta - Elsa Imelda; Rousilita Suhendah; Ivan Kanel; Sri Sundari; Kartini Kartini (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Indonesia’s expanding digital-payment ecosystem has increased the availability of e-wallets, mobile banking, and QRIS, yet adoption remains shaped by users’ assessments of convenience, safety, capability, and provider-led prompts. Objective: This study investigates how perceived ease of use, perceived security, perceived behavioral control, and behavioral nudges relate to digital payment adoption among users in Jakarta. Methods: A quantitative cross-sectional survey was administered to 249 eligible digital-payment users selected through purposive sampling. The model was estimated using PLS-SEM in SmartPLS 4. Results: All proposed relationships were positive and statistically significant: perceived ease of use (β = 0.312, p < .001), perceived security (β = 0.276, p < .001), perceived behavioral control (β = 0.298, p < .001), and behavioral nudges (β = 0.214, p = .001). The predictors jointly explained 87.4% of the variance in adoption. Conclusion: Adoption in Jakarta is associated with both technology evaluations and behavioral conditions. Providers should make services intuitive, communicate security safeguards clearly, strengthen users’ confidence, and apply transparent, non-coercive nudges.